On the Commoditization of Artificial Intelligence - Abonamah, Abdullah A.; Tariq, Muhammad Usman; Shilbayeh, Samar (Frontiers in Psychology, 2021)
As Artificial Intelligence's potential and pervasiveness continue to increase, its strategic importance, effects, and management must be closely examined. Societies, governments, and business organizations need to view Artificial Intelligence technologies and their usage from an entirely different perspective. AI is poised to have a tremendous impact on every aspect of our lives. Therefore, it must have a broader view that transcends AI’s technical capabilities and perceived value, including areas of AI’s impact and influence. Nicholas G. Carr’s seminal paper “IT Does not Matter (Carr, 2003) explained how IT's potential and ubiquity have increased, but IT’s strategic importance has declined with time. AI is poised to meet the same fate as IT. In fact, the commoditization of AI has already began. This paper presents the arguments to demonstrate that AI is moving rapidly in this direction. It also proposes an artificial intelligence-based organizational framework to have value-added elements for lowering the impact of AI commoditization.